EFEKTIVITAS PENGGUNAAN MEDIA KEMASAN MAKANAN RINGAN TERHADAP KEMAMPUAN MEMBACA PERMULAAN MURID KELAS I UPT SD NEGERI 13 BANGKALA BARAT - Nur Jannah Susang; Bahrun Amin; Tasrif Akib (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This study aims to determine the Effectiveness of Using Snack Food Packaging Media on Beginning Reading Ability of Class I UPT SD Negeri 13 Bangkala Barat in 2023. This type of research is a pre-experimental design study, One-Group PreTest PostTest Design. The sampling technique used is the total sampling technique, by making the population as a sample, namely 20 students. Data collection techniques in this study used tests and observations. The data analysis used is descriptive data analysis and inferential data analysis. The results of inferential statistical analysis using the t test formula, it is known that the calculated t value obtained is 3.04 with a frequency of dk = 20 –1 = 19, at a significance level of 0.05 obtained t table = 1.729. So, t count > t table or the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. This means that the use of snack food packaging media is effective on the initial reading ability of Class I UPT SD Negeri 13 Bangkala Barat students.